Rotating Trio Exchange Model In Progress Learning on the Formation of Students' Social Values - A Iqbal; Ali Hanafi; Muamar Asykur (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to describe the implementation of the RTE model, students' experiences in the formation of social values, and the role of teachers in facilitating and guiding the RTE learning process at the UPT SMPN SATAP Tarupa No. 38 Kepulauan Selayar. This study uses a qualitative approach with a phenomenological research type. Data were collected through interviews, observations, and documentation, with Civics teachers as key informants and grade VIII students as key informants. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed that the implementation of RTE was carried out through the formation of trio groups, structured role rotation, discussion time management, and two-way discussions accompanied by reflection on student experiences. Student experiences showed the development of group role responsibility, interpersonal empathy, teamwork, respect for differences, and communication confidence. Teachers acted as facilitators of group interactions, guides for student participation, reinforcers of social responsibility, instillers of empathy, reflectors of social experiences, and models of social values. Thus, the RTE model supports the formation of students' social values ​​through participatory, communicative, and reflective learning experiences.